2020
DOI: 10.3390/su12239797
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Agenda 2030: Future-Oriented Mechanisms in Localising the Sustainable Development Goals (SDGs)

Abstract: Given the complex nature of the UN’s Sustainable Development Goals (SDGs), there are increasing calls for new inclusive and bottom-up governance mechanisms in building a relationship between governments and their citizens, in particular, the youth, to localise the 2030 Agenda. But such successful bottom-up multi-stakeholder engagement tools have yet to emerge in practice. Hence, of specific interest in this study is exploring bottom-up approaches useful for localising the SDGs and harnessing real transformativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…We review the papers that were published in one year before data collection. The results show that literature reviews [ 8 , 16 , 25 , 35 , 43 , 51 , 55 , 67 , 79 , 91 ] and case studies [ 2 , 4 , 9 , 17 , 24 , 30 , 54 , 61 , 83 , 88 ] are still the predominant research methods, although more sophisticated methods of research are starting to become adopted, though, such as systematic literature reviews [ 15 ], comparative analysis of the investment criteria and other reports [ 33 ], interviews [ 23 , 81 ] and surveys [ 32 , 50 , 66 , 90 ].…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…We review the papers that were published in one year before data collection. The results show that literature reviews [ 8 , 16 , 25 , 35 , 43 , 51 , 55 , 67 , 79 , 91 ] and case studies [ 2 , 4 , 9 , 17 , 24 , 30 , 54 , 61 , 83 , 88 ] are still the predominant research methods, although more sophisticated methods of research are starting to become adopted, though, such as systematic literature reviews [ 15 ], comparative analysis of the investment criteria and other reports [ 33 ], interviews [ 23 , 81 ] and surveys [ 32 , 50 , 66 , 90 ].…”
Section: Resultsmentioning
confidence: 87%
“…Grafius et al [ 24 ] argue that research efforts and management strategies have so far focused on risks and negative aspects of the complexity of the systems perspectives,however, their case study review identified how interdependencies can also be seen positively, representing possibilities to increase organisational resilience and sustainability. The integrated social innovation and scenario-thinking mechanism was developed by Bonsu et al [ 4 ] as a bottom-up tool for empowering citizens, including youth and decision-makers, in delivering sustainable development goals, plans, policies and programmes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the UN's SDGs, including SDG2, there is a growing desire for bottom–up governance methods by helping governments and individuals in establishing relationships to make progress on the localization of the 2030 Agenda (Bonsu et al 2020 ). Despite the importance of bottom–up governance mechanisms, there were only isolated mentions (by one participant only) of a point on improving such approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Agency is another major concern. There is a growing call, in academia, for bottom–up governance practices in achieving sustainable development goals (Bonsu et al 2020 ). Nevertheless, our interview results show that such practices are scarce in the Caribbean food system.…”
Section: Discussionmentioning
confidence: 99%